The implementation and impacts of national standards for comprehensive care in acute care hospitals: An integrative review - Beibei Xiong; Christine Stirling; Melinda Martin-Khan (Elsevier, 2023)
Objectives: To synthesise current evidence addressing implementation approaches, challenges and facilitators, and impacts of national standards for comprehensive care in acute care hospitals. Methods: Using Whittemore & Knafl's five-step method, a systematic search was conducted across five databases, including Medline (EBSCO), CINAHL (EBSCO), Cochrane Library, Web of Science, and Scopus, to identify primary studies and reviews. In addition, grey literature (i.e., government reports and webpages) was also searched via Google and international government/organisation websites. All searches were limited to January 1, 2000 to January 31, 2023. Articles relevant to the implementation or impacts of national standards for comprehensive care in acute care hospitals were included. Included articles underwent a Joanna Briggs Institute quality review, followed by qualitative content analysis of the extracted data adhering to PRISMA reporting guidelines. Results: A total of 16 articles were included in the review (5 primary studies, 5 government reports, and 6 government webpages). Three countries (Australia, Norway, and the United Kingdom [UK]) were identified as having a national standard for comprehensive care. The Australian standard contains a unique component of minimising patient harm. Norway does not have a defined implementation framework for the standard, whereas Australia and the UK do. Limited research suggests that challenges in implementing a national standard for comprehensive care in acute care hospitals include difficulties in implementing governance processes, end-of-life care actions, minimising harms actions, and developing comprehensive care plans with multidisciplinary teams, the absence of standardised care plans and patient-centred goals in documentation, and excessive paperwork. Implementation facilitators include a new care plan template using the Identify, Situation, Background, Assessment and Recommendation framework for handover, promoting efficient documentation, clinical decision-making and direct patient care, and proactivity among patients and care professionals with collaboration skills. Limited research suggests introducing the Australian standard demonstrated some positive effects on patient outcomes. Conclusion: The components and implementation approaches of the national standards for comprehensive care in Australia, Norway and the UK were slightly different. The scarcity of studies found during the review highlights the need for further research to evaluate the implementation challenges and facilitators, and impacts of national standards for comprehensive care in acute care hospitals.